‘Daddy I do’: purity balls, evangelical ideals of virginity, family values, and whiteness - Kim-Kort, Mihee (Theology & sexuality, 2023)
Purity balls, which were a part of larger evangelical Protestant social outreach projects in the U.S., illustrate the social and political impact of a theology of ‘family values,' constructed by cultural liturgies that prescribe parameters around sexual activity, gender identity, and marriage. These theological practices also perpetuate racialized structures by upholding purity specifically as whiteness. Examining this ritual as a representative segment of not only evangelical movements but projects around American national identity provides a meaningful exploration into the dynamic between religion and secularism with implications for how evangelicalism shapes social and political realities by delineating personhood. I analyze purity balls as presented in two documentaries, The Virgin Daughters and Virgin Tales and critique the effects of purity in terms of virginity and marriage, the figuration of gender through the female body, an ethos based on ‘family values,’ and the formation of U.S. American identity and white femininity.